Essays on Religion and Political Behavior: How Religion Facilitates Political Development and Change - (:unkn) unknown (My University, 2014)
This dissertation investigates several unexplored topics regarding the influence of Americans' religion on their political attitudes and behaviors. First, it posits that religious socialization enables and constrains the development of a child's party identification and moral issue attitudes over time. Using the Youth Parent Socialization Panel Study, three indicators of a parent's religion are employed to predict a child's politics early in life, over time, and across generations. The results show an evolving role of parental religious socialization on individuals' party identification and moral issue attitudes. In particular, for newer generations, parental religious beliefs have supplanted historical, religious-belonging-based religious measures in predicting their child's political attitudes. The results provide a possible mechanism for the newly emerging religio-political conflicts observed today. Second, there is an analysis of how changes in individuals' religiosity of beliefs and behaviors relate to changes in their political attitudes and behaviors over time. Theories of social identity and cognitive consistency imply that if an individual changes one of these factors, they should also update the other. Continuing to employ the Youth Parent Study, the results show that as individuals become more religiously traditional they are more likely to be affiliated with the Republican Party and take increasingly conservative positions on moral issues. Whereas, individuals who become religiously secular gravitate toward the Democrats and take increasing liberal positions on moral issues. But the connection between religiosity and political attitudes only emerged starting in the 1980s. These results challenge research that argues religio-political sorting primarily happens for the youngest generations. Finally, this research explores the well-cited association between religious attendance and political participation. Three separate theoretical possibilities are considered: a direct, indirect, and null relationship. The analysis shows that individuals who regularly attend religious services are more likely to engage in both civic and political activities than occasional or infrequent attenders. But the relationship between religious attendance and political participation is primarily indirect, via civic engagement, and far weaker than stated by earlier literature. Taken together, each of these topics fills a significant gap in the literature by exploring some of the processes in which religion affects politics early in life and over an individual's lifecycle.
Keywords: Moral Issues; Party Identification; Political Behavior; Political Participation; Religion; Socialization